Pengaruh Kualitas Pelayanan Publik terhadap Kepercayaan Masyarakat (Public Trust) Melalui Kepuasan Masyarakat Sebagai Variabel Mediasi di Kantor Kelurahan Karijawa - Nurul Sidikah; Nurut Hayat; Asmawati Asmawati (Jurnal Manajemen Riset Inovasi, 2026)
This study aims to analyze the effect of public service quality on public trust through public satisfaction as a mediating variable at the Karijawa Subdistrict Office. This is a quantitative study using an explanatory research approach. Using accidental sampling and the Lemeshow formula, a sample of 96 respondents was obtained from a total population of 1,343 service users. Primary data were collected via a 1–5 Likert-scale questionnaire and supplemented by secondary data from documentation and interviews. Data analysis employed the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method, involving evaluation of the outer model (validity and reliability) and the inner model (hypothesis testing via bootstrapping). The study concluded that the quality of public services at the Karijawa Subdistrict Office has a positive and significant impact on increasing public trust, both directly and indirectly. Reliable, responsive, transparent, and friendly service has proven to be the primary factor driving resident satisfaction. The emotional satisfaction consistently felt by the community regarding these administrative services eventually crystallizes and acts as a very strong mediating bridge in constructing, strengthening, and solidifying public trust and residents’ legitimacy regarding the credibility of the bureaucracy at the Karijawa Subdistrict Office. Therefore, the continuous improvement of service quality is the key to maintaining the stability of public trust at the sub-district level.